Effects of Salinity Level on The Growth, Filtration Rate and Survival of Pearl Oyster (Pinctada maxima) Spats - Ramadhan, Devi Aulia; Mukhlis, Alis; Diniariwisan, Damai (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Pearl oysters (Pinctada maxima) are an aquaculture commodity with high economic value. Large-scale production of pearl oyster seeds remains a challenge due to low growth and survival rates. Salinity is an environmental factor that greatly influences growth, feed filtration rate and survival of bivalves. This study aims to evaluate the effect of salinity levels on the growth, survival and filtration rate of pearl oyster spat. Pearl oyster spats measuring 2.14 ± 0.77 mm (dorso-ventral) were reared for 21 days at salinities of 26, 30, 34, and 38 ppt with a single feed of Chaetoceros amami with an initial density of 20,000 cells/ml. The results showed that a salinity of 34 ppt produced the highest growth and was significantly different (p < 0.05) compared to other salinities with an absolute growth value of 6.18 ± 0.25 mm, relative growth of 288.8 ± 11.5% and the daily specific growth rate is 6.68 ± 0.15% per day. The feed filtration rate value at a salinity of 34 ppt was 126.76 ml/hour/individual with a survival rate of 94.22% where these two parameters were also significantly different compared to other salinity treatments. There is a close relationship between growth, filtration rate and survival of spat with the salinity level of the rearing medium. This research shows that salinity of 34 ppt is the optimal condition to support growth, feed filtration rate, and survival of pearl oyster spat.